Terapi Herbal untuk Pencegahan Adhesi Peritoneal Pascaoperasi: Tinjauan Mekanistik Studi Praklinis - Inzaghi, Ika Silviadewi; Mahati, Endang; Budiono, Bernardus Parish (Poltekkes Kemenkes Bandung, 2026)
Background: Postoperative peritoneal adhesions remain a common complication of abdominal and pelvic surgery and may cause bowel obstruction, infertility, chronic pain, and difficult reoperation. Objective: This review synthesized evidence on herbal therapeutics for adhesion prevention. Methods: A comprehensive search of PubMed, Scopus, and Google Scholar for 2015-2025 publications used keywords related to postoperative adhesions and herbal therapy. English-language full-text in animal experimental studies with peritoneal adhesion induction and herbal interventions were included; non-herbal interventions, duplicate reports, non-postoperative adhesions, abstracts only, non-English papers, and retracted articles were excluded. Results: A total of 169 records were identified, and after duplicate removal, title and abstract screening, and full-text eligibility assessment, 29 studies were included in the qualitative review. Curcumin consistently reduced inflammatory signaling, oxidative stress, collagen deposition, and adhesion scores through NF-kB modulation and antioxidant effects. Ginger and gingerol lowered TNF-α, IL-6, TGF-β1, VEGF, and malondialdehyde, indicating anti-inflammatory, antifibrotic, and anti-angiogenic activity. Rosmarinus officinalis reduced cytokines, oxidative markers, and TGF-β1 in rat models. Bletilla striata, frankincense, and polyherbal formulas showed additional wound-healing, anti-inflammatory, and pro-fibrinolytic effects. Conclusion: Herbal therapeutics appear promising as adjunctive strategies for preventing postoperative adhesions; however, the evidence remains heterogeneous and is dominated by animal and in vitro studies. Standardized formulations, safety evaluation, and well-designed clinical trials are needed before wider clinical application.